2023
DOI: 10.1002/dmrr.3729
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary vitamin intake and mortality in US adults with diabetes: A prospective cohort study

Wei Liu,
Shuting Cao,
Da Shi
et al.

Abstract: AimsTo explore the association of dietary vitamin intake from food and/or supplement with mortality in US adults with diabetes.Materials and MethodsThis prospective cohort study was conducted on 5418 US adults with diabetes from the National Health and Nutrition Examination Survey 1999–2018. Vitamin intake from food and supplements was estimated via dietary recall. Sufficient intake from food or food + supplement was defined as ≥ estimated average requirement (EAR) and ≤ tolerable upper intake level (UL), insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Regarding the population nutrition status of B vitamins, in comparison to the recommended nutrient intake (RNI) for individuals older than 50 years old in the Chinese Dietary Reference Intakes (2023 edition), the overall intake levels of vitamin B3, B9, and B12 were higher than the recommended levels, while vitamin B1, B2, and B6 intakes were slightly below the recommendations. Additionally, compared to the National Health and Nutrition Examination Survey (NHANES) database, the levels of six B vitamins are similar between the Chinese and US residents [ 33 , 34 , 35 ]. Consistent with numerous epidemiological studies, our research identified strong links between a single B vitamin intake and incident T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the population nutrition status of B vitamins, in comparison to the recommended nutrient intake (RNI) for individuals older than 50 years old in the Chinese Dietary Reference Intakes (2023 edition), the overall intake levels of vitamin B3, B9, and B12 were higher than the recommended levels, while vitamin B1, B2, and B6 intakes were slightly below the recommendations. Additionally, compared to the National Health and Nutrition Examination Survey (NHANES) database, the levels of six B vitamins are similar between the Chinese and US residents [ 33 , 34 , 35 ]. Consistent with numerous epidemiological studies, our research identified strong links between a single B vitamin intake and incident T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia is the fifth country in the world with the highest number of diabetes cases, following China, India, Pakistan, and the United States [3]. Diabetes has a significant risk of mortality [4], [5], amputation [6], and other complications that can disrupt normal bodily functions [7].…”
Section: Introductionmentioning
confidence: 99%